Freezing Studies on a Model System and Quality Changes in Frozen Malaysian Fish - Abdullah, Mohd. Ismail (1985)
Variations in the definition of freezing time do not provide a universally accepted definition which adequately describe the freezing rate. A "volume average freezing time" was derived as an alternative definition of freezing time which gave a linear relationship with frozen depth . The majority of the experimental values was found to fall within 20% of the predicted figures using the derived formula . Proximate analysis , objective and organoleptic tests were done on Chub Mackerel, Yellow-banded Trevally and Notched Threadf in Bream. Samples of gutted and ungutted fish were frozen fast and slow, and stored in the glazed and unglazed conditions at - 20˚C for 16 to 24 weeks. At intervals various chemical indices of deterioration were determined and taste-panel assessment performed. The data on lipid oxidation, protein denaturation and pH changes were related to textural, flavour, odour and general acceptability performances. The quality of canned frozen Chub Mackerel were also determined. Malonaldehyde production in Threadfin Bream (0.8% fat content) was low and similar to that in Yellow-banded Trevally (9.7% fat content), whereas values for Chub Mackerel (2.1% fat content) was higher than both the former two species and were produced over a shorter storage period. These differences were also shown to conform to odour and flavour scores for all the three species . The protein solubility in Threadfin Bream (pH = 6.8) and Yellow-banded Trevally (pH = 6.15) remained low during the storage period which results in a softer texture. In comparison, Chub Mackerel (pH = 6.15) had a firmer texture as protein solubility remained higher during the storage period. Threadfin Bream and Yellow-banded Trevally also gave higher general acceptability scores over that of Chub Mackerel at the same storage period, and the storage life of the two former species were longer than the latter. TBA values of canned Chub Mackerel prepared from frozen fish increased during subsequents to rage, and proportional to the length of frozen storage period before canning. The general acceptability scores decreased with increase in period of frozen storage before canning. The limit of frozen storage period for Chub Mackerel before canning is one month or less for an acceptable canned product to last for not more than three months. Generally fresh fish gave a better canned product than frozen fish.